Hubungan Pernikahan Usia Dini Dengan Kejadian Partus Lama Dan BBLR Di Wilayah Kerja Puskesmas Kedungjati - Sahara, Rizki (Indonesian Journal of Health Community, 2025)
Early marriage persists as a common issue in developing nations, particularly in Indonesia. This practice elevates the risk of several complications during pregnancy, delivery, and the postpartum period, primarily due to the underdeveloped reproductive systems of young women. This research aimed to determine the significance and nature of the connection between early marriage and the prevalence of prolonged labor and low birth weight (LBW). A correlative descriptive study with a retrospective design was conducted, utilizing secondary data from medical records within the Kedungjati Health Center's operational area, encompassing labor details and maternal age. The Spearman correlation test was employed to analyze the strength of association between the variables. The findings indicated a moderate correlation between early marriage and both prolonged labor (r = -0.326, negative correlation) and LBW (r = 0.440, positive correlation). These results suggest that early marriage is associated with a higher likelihood of these adverse health outcomes. Consequently, the study concludes that the health consequences linked to early marriage can be substantial, emphasizing the necessity for enhanced monitoring and intervention by relevant stakeholders.